Benzyl imidazolium-based ionic liquids for the removal of phenols from non-aqueous solution / Nadiah Sidek - Nadiah , Sidek (2018)

(untitled)
Two types of method were studied to remove phenol from non-aqueous solution namely; liquid-liquid extraction (LLE) and adsorption technique in which hexane was used as the model oil. Three types of benzyl imidazolium-based room temperature ionic liquids (RTILs) were synthesized and used as extractants in LLE while silica-titania mixed oxide with RTILs were used as adsorbents in adsorption technique. In LLE technique, 1-allyl-3-benzylimidazolium chloride ([Abzim][Cl]) was used in the optimization of parameters including influence of phase volume ratio between IL and model oil, time, temperature, type of model oils and selectivity study. Based on three different types of substituents on benzyl imidazolium-based ILs, allyl substituent showed excellent phenol removal efficiency compared to vinyl and benzyl substituents. The 1H NMR spectra revealed that the distance of chloride anion (Cl-) from carbon C2 on imidazolium ring played a vital role in determining the performance of the ILs to form hydrogen bonding with phenol besides the presence of π-π interaction. The performance of [Abzim][Cl] was excellent even in synthetic oil where phenol (Ph), 2,4-dichlorophenol (2,4-DCP) and 2,4-dinitrophenol (2,4-DNP) can be removed even in the presence of other aromatic compounds such as fluorene and fluoranthene. On the other hand, silica-titania mixed oxide with monocationic and dicationic ILs were synthesized as adsorbents. These compounds then underwent preliminary study for removal of phenol via adsorption process. However, the result revealed that the performance of these adsorbents were not as good as RTILs as extractants in LLE. It can be concluded that the developed LLE method is the best method to remove phenols from oil compared to adsorption technique.